Piper sarmentosum water extract attenuates diabetic complications in streptozotocin induced sprague-dawley rats - Farida Hussan,; Nur Nazilah Mat Zin,; Mohd Ramdzi Zullkefli,; Yow, Siew Choon; Noor Adibah Abdullah,; Teoh, Seong Lin (Universiti Kebangsaan Malaysia, 2013)
Piper sarmentosum has been shown to possess antihyperglycemic effect. The effect of water extract of PS leaves was determined on the diabetic complications in streptozotocin induced rats. Eighteen male Sprague Dawley rats (n=18) were randomly divided into three groups with six rats each, namely, control, diabetic untreated and PS treated diabetic groups. Diabetes was induced with intramuscular injection of STZ (50 mg/kg). Ten days following the induction, the diabetes was confirmed with fasting blood sugar level more than 8 mmol/L and PS extract was administered orally (0.125 g/kg) for 28 days. The left kidneys were collected to analyze. The body weight and kidney weight index showed significant differences between control and diabetic groups (p<0.05). However, the lesser extent of body weight gain was observed in diabetic group compared with the control groups. The fasting blood sugar level was reduced in PS treated group. The percent area occupied by the glomerulus over a renal corpuscle was found to be 74.5% in DPS, 72% in DNT and 75% in C group; however it was statistically insignificant. Histological study revealed marked inflammatory cells infiltration and glomeruli contraction with widened urinary spaces revealed in DNT group following 28 days of hyperglycemic state whereas the DPS group showed features of improvement. The water extract of PS leaves has the potential preventive effect on the diabetic nephropathy by reducing hyperglycemia.